2008
DOI: 10.1111/j.1469-1809.2008.00476.x
|View full text |Cite
|
Sign up to set email alerts
|

PKU in Minas Gerais State, Brazil: Mutation Analysis

Abstract: SummaryThis work was undertaken in order to ascertain the PKU mutational spectrum in Minas Gerais, Brazil, the relative frequency of the mutations in the State and the origin of these mutations by haplotype determination. Minas Gerais is a trihybrid population formed by miscegenation from Europeans, Africans and Amerindians. All 13 exons of the PAH gene from 78 PKU patients were analyzed, including splicing sites and the promoter region. We identified 30 different mutations and 98% of the PAH alleles were esta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
22
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 34 publications
(36 reference statements)
7
22
0
Order By: Relevance
“…Kinetic studies of the mutant protein with the V388M mutation showed reduced affinity of the enzyme for L-Phe and tetrahydrobiopterin (Leandro et al, 2000). This mutation is relatively common in Brazil, Portugal, and Spain (Santos et al, 2006). The Q375R mutation is a new sequence variant that is reported in the present study for the first time, and was entered into the PAH and HGMD databases.…”
Section: Discussionmentioning
confidence: 95%
“…Kinetic studies of the mutant protein with the V388M mutation showed reduced affinity of the enzyme for L-Phe and tetrahydrobiopterin (Leandro et al, 2000). This mutation is relatively common in Brazil, Portugal, and Spain (Santos et al, 2006). The Q375R mutation is a new sequence variant that is reported in the present study for the first time, and was entered into the PAH and HGMD databases.…”
Section: Discussionmentioning
confidence: 95%
“… Data were quoted from Santos et al. (), in Minas Gerais, Brazil (MG), Acosta et al. (, ), in São Paulo, Brazil (SP), Perez et al.…”
Section: Resultsmentioning
confidence: 99%
“…Approximately 6‐9 different alleles account for the majority of mutant chromosomes described in previous PKU population genetics studies done in Latin America – Brazil (Acosta, Silva, Carvalho, Gomes, & Zago, ; Santana da Silva et al., ; Santos et al., ), Chile (Hamilton et al., ), and Mexico (Vela‐Amieva et al., ), and the Iberian Peninsula (Aldamiz‐Echevarria et al., ; Couce et al., ; Rivera et al., ); the remainder are minor, rare, and even private disease‐causing alleles.…”
Section: Introductionmentioning
confidence: 99%
“…Genomic DNA isolation and mutation analysis was done previously by PCR and RFLP or based on single-strand conformation polymorphism and sequencing (Santos et al, 2006(Santos et al, , 2008.…”
Section: Genotypingmentioning
confidence: 99%
“…In Minas Gerais State, in southeastern Brazil, nine mutations account for 80% of the PKU alleles (Santos et al, 2006(Santos et al, , 2008, which facilitates investigation of their phenotypic effect. Some of the mutations that are common in Minas Gerais, such as V388M, IVS2+5G>A, and IVS2+5G>C, are little known elsewhere.…”
Section: Introductionmentioning
confidence: 99%